Very high VOC and FF of CdTe thin‐film solar cells with the applications of organo‐metallic halide perovskite thin film as a hole transport layer. (10th July 2020) - Bhandari, Khagendra P.; Alfadhili, Fadhil K.; Bastola, Ebin; Watthage, Suneth C.; Song, Zhaoning; Liyanage, Geethika K.; Phillips, Adam J.; Heben, Michael J.; Ellingson, Randy J.
Abstract: We fabricate and characterize methylammonium lead halide perovskite film as a novel back contact to CdTe thin‐film solar cells. We apply ~0.75 μm perovskite film at the interface of CdCl2 ‐activated and Cu‐doped CdTe surface and complete the device with Au back contact. We use Cu/Au back contact as a reference to compare results with novel back contact. Our investigation shows that incorporation of thin layer of perovskite film before the back contact metal reduces back contact barrier effect and improves fill factor (FF) and open‐circuit voltage (VOC ) of the solar cells. Our low temperature JV results prove that thin‐film perovskite is a very necessary component in CdTe solar cells to reduce back contact barrier, to minimize interface or surface recombination, to improve collection efficiencies, and to increase the efficiency of solar cells. Our best device shows 7% increase in VOC to 0.875 V and ~7% increase in FF with the highest FF of 81%, and solar cell's efficiency finally increases by 10% with the use of MAPb(I1‐x Brx )3 as an interface layer. Abstract : 1. Back contact management in CdTe thin film solar cell is very important to gain its full benefits. 2. Organo‐metallic halide perovskite, MAPb (I1‐x Brx )3 thin film can be a promising hole transport material in CdTe thin film solar cell. An increase of >10% in photo‐conversion efficiency of CdTe solar cell is obtained with the introduction of Cu/MAPb(I1‐x Brx )3 /Au back contact with respect to standard Cu/Au back contact.